The Image of The Police as A Dispositional Group In The Light of Research - Iwona OSMOLSKA (Communications of International Proceedings, 2024)
The image of a police disposition group is formed in the public's consciousness and is important from the moment of first contact and is then shaped over many years. It is influenced both by history, information provided by the mass media and personal contact of citizens with the police officer. The Polish uniformed formations, including the Police (Misiuk et al 2020:601-616), have undergone radical changes since 1989. A positive image inspires public trust, a negative image results in distrust and sometimes even hostility towards the formation. A flattering image of the police also becomes a determinant in the fight against crime and pathological phenomena. The main premise of the publication is based on the statement that a positive image of the Police influences its effectiveness in providing security and maintaining public order. Undertaking activities by the Police to shape its positive image is therefore an extremely important element for its functioning.
Keywords: image; police; public opinion